Políticas de apoio à inovaç\~ao no Brasil: Uma análise de sua evoluç\~ao recente - Bruno César Araújo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This article aims to analyze the evolution of innovation policies in Brazil, as well as its measures of direct and indirect support and its institutional framework. Despite the explicit government efforts since 2003 and the so-called scientific-boom, Brazilian innovation indicators have not changed dramatically in the last decade compared to earlier. Some hypotheses to explain this are discussed in the last section, which should be objects of further exploration: i) innovation indicators in Brazil are limited by the industry structure; ii) even with positive impacts on innovation efforts reported by the literature, the scale of instruments to support innovation is very low compared to the potential audience, and the focus of the instruments is not clearly directed to companies with innovative potential; and iii) there are institutional barriers that hinder the effectiveness of the instruments.
Keywords: 330; innovation policies; innovation indicators; impact evaluation of public policies; Innovationspolitik; Brasilien